Completing the Solution of the Directed Oberwolfach Problem with Two Tables - Horsley, Daniel; Lacaze-Masmonteil, Alice (The Electronic Journal of Combinatorics, 2026)
We address the last outstanding case of the directed Oberwolfach problem with two tables of different lengths. Specifically, we show that the complete symmetric directed graph K^*_n admits a decomposition into spanning subdigraphs comprised of two vertex-disjoint directed cycles of length t_1 and t_2, respectively, where t_1{4,6}, t_2 is even, and t_1+t_214. In conjunction with recent results of Kadri and Šajna, this gives a complete solution to the directed Oberwolfach problem with two tables of different lengths.